EXPLORING THE MEANING OF REGIONAL LITERATURE OF JEMBER PENDALUNGAN COMMUNITY - Dzarna Dzarna (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2020)
The Pandhalungan community is a hybrid society; it is social intercourse of cultures between Madurese and Javanese in Jember. They have their regional literature and used to pronounce it in their daily life. It is a legacy of their ancestors and needs to to be preserved since it has many interesting moral values. Nevertheless, due to the modern era, this regional literature is currently in danger, especially to young people. This is very unfortunate, as it only exists in Jember. This research aimed to describe the meaning beyond the Pandhalungan literature, from its meanings and moral values. This was a qualitative study that its data were collected through interviews. The data analysis technique of this research was using data reduction, data presentation, and conclusion. Triangulation was used to test its validity. Based on the interviews, it was found that both Javanese and Madurese regional literature had denotative, connotative meanings, and also moral values. It is included moral values relate to humans, as well as humans with other people. While moral values related to God was not found. On the other hand, based on the theory of Nurgiyantoro Madura literature contained all moral values, including the relationship with the man, man to man, and man to God.